Targeting Alzheimer’s Disease Neuro-Metabolic Dysfunction with a Small Molecule Nuclear Receptor Agonist (T3D-959) Reverses Disease Pathologies - Tong, Ming (J Alzheimers Dis Parkinsonism, 2016)
BACKGROUND: Alzheimer’s disease (AD) could be regarded as a brain form of diabetes since insulin resistance and deficiency develop early and progress with severity of neurodegeneration. Preserving insulin’s actions in the brain restores function and reduces neurodegeneration. T3D-959 is a dual nuclear receptor agonist currently in a Phase 2a trial in mild-to-moderate AD patients (ClinicalTrials.gov identifier NCT02560753). Herein, we show that T3D-959 improves motor function and reverses neurodegeneration in a sporadic model of AD. METHODS: Long Evans rats were administered intracerebral (i.c.) streptozotocin (STZ) or normal saline (control) and dosed orally with T3D-959 (1.0 mg/kg/day) or saline for 21 or 28 days. Rotarod tests evaluated motor function. Histopathology with image analysis was used to assess neurodegeneration. RESULTS: T3D-959 significantly improved motor performance, and preserved both cortical and normalized white matter structure in i.c STZ-treated rats. T3D-959 treatments were effective when dosed therapeutically, whether initiated 1 day or 7 days after i.c. STZ. CONCLUSION: T3D-959’s targeting neuro-metabolic dysfunctions via agonism of PPAR delta and PPAR gamma nuclear receptors provides potential disease modification in AD.